-7(8-6m)=-266

Simple and best practice solution for -7(8-6m)=-266 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(8-6m)=-266 equation:


Simplifying
-7(8 + -6m) = -266
(8 * -7 + -6m * -7) = -266
(-56 + 42m) = -266

Solving
-56 + 42m = -266

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 42m = -266 + 56

Combine like terms: -56 + 56 = 0
0 + 42m = -266 + 56
42m = -266 + 56

Combine like terms: -266 + 56 = -210
42m = -210

Divide each side by '42'.
m = -5

Simplifying
m = -5

See similar equations:

| -8u+8=-10u | | 6t-5t=t | | 2z+7=z | | -5u=-6u-6 | | -3v+5=-8v | | 8g+10=6g | | 200=270+2p | | 4n-3=4n | | 4-3y=-3y | | 7.8(s+2.1)-8.9=2.1s-9.5 | | 9+7b=6b | | 1=-270+2p | | 14+8j+19=19j-11 | | -7k-16=-11k+20 | | -14n-18=-20n | | 200=-270+2p | | 2y-y=-1 | | -p+5=12 | | 8=j-6 | | u=-7+8u | | -5d-9=-7d+5 | | 8n-n=10 | | X(20-2x)=50 | | -7+3g=4g | | 7=5m-2m | | 3=7n-5n | | -4v-10-6v=-6v+10 | | 21=7r-2r | | 8-2c=-3c | | 11r-4r=6 | | 3=4x-3x | | 8x-5=42 |

Equations solver categories